For the Term of His Natural Life - Clarke, Marcus Andrew Hislop, 1846-1881 (Salt Lake City, UT : Project Gutenberg, 2002)
"For the Term of His Natural Life" by Marcus Andrew Hislop Clarke is a novel published in 1874. Set in early colonial Australia, it follows Rufus Dawes, a young British aristocrat wrongly convicted of murder and transported to a brutal penal colony. Based on Clarke's research and visits to Port Arthur, the story depicts the harsh realities of convict life through a series of dramatic events involving betrayal, attempted escapes, and unlikely survival. The novel vividly portrays the inhumane treatment of prisoners in Australia's convict era. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/For_the_Term_of_His_Natural_Life
Release date is 2002-09-01
Produced by Col Choat, and David Widger
Keywords: Historical fiction; Australia -- Fiction; Prisoners -- Fiction; Penal colonies -- Australia -- Fiction; Penal transportation -- Fiction